P1239SHORT- AND LONG-TERM OUTCOME OF END-STAGE RENAL DISEASE PATIENTS WITH ACUTE MYOCARDIAL INFARCTION. (6th June 2020) - Kida, Hirota; Hikoso, Shungo; Sunaga, Akihiro; Bolrathanak, Oeun; Kojima, Takayuki; Dohi, Tomoharu; Kitamura, Tetsuhisa; Okada, Katsuki; Suna, Sinichiro; Nakatani, Daisaku; Mizuno, Hiroya; Sakata, Yasushi
Abstract: Background and Aims: End-stage renal disease (ESRD) patients frequently have the coronary artery disease. However, the short- and long-term outcome of ESRD patients with acute myocardial infarction (AMI) is little known. The aim of this study was to clarify it. Method: Using the database of the Osaka Acute Coronary Insufficiency Study (OACIS), 8702 consecutive AMI patients (male: 75.2%, mean age: 66.9±12.2yrs) from 2002 to 2013 were analyzed. We classified these patients into two groups, those with ESRD [ESRD group (n=271)] and without ESRD [No-ESRD group (n=8431)] and examined in-hospital or long-term all-cause mortality. ESRD was defined as eGFR<15ml/min/1.73m 2 . Results: ESRD group had higher frequency of diabetes (59.3% vs 37.8%, p<0.01), hypertension (90.1% vs 63.3%, p<0.01), Killip class≧2 (40.1% vs 21%, p<0.01), multi-vessel disease (69.3% vs 50.8%, p<0.01), and lower frequency of peak CK>3000 (21.7% vs 32.4%, p<0.01) than No-ESRD group. Mean follow-up period was 1041±721 days. In hospital mortality of ESRD group was 27% and No-ESRD group 7.2%. In patients who discharged alive (8027 patients), 1-year mortality of ESRD group was 12.2% and No-ESRD group 3.3%, 3-year mortality of ESRD group was 29.3% and No-ESRD group 8.7%. Kaplan-Meier analysis revealed that the all-cause mortality (log-rank p<0.01) was significantly higher in ESRD group than No-ESRD group. In ESRD patients who discharged alive (203patients), Cox univariate analysis after multiple imputation revealed that peak CK>3000 was significantly associated with an increased risk of mortality (Hazard ratio 2.67, 95% confidence interval 1.18to 6.07, p=0.031). Conclusion: In patients with AMI, ESRD was significantly associated with worse short- and long-term outcome, suggesting that careful treatment might be required in ESRD patients with AMI, especially had peak CK>3000.